2007
DOI: 10.1109/tpwrs.2006.889078
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Statistical Method for Wind Power Forecasting

Abstract: This paper presents an advanced statistical method for wind power forecasting based on artificial intelligence techniques. The method requires as input past power measurements and meteorological forecasts of wind speed and direction interpolated at the site of the wind farm. A self-organized map is trained to classify the forecasted local wind speed provided by the meteorological services. A unique feature of the method is that following a preliminary wind power prediction, it provides an estimation of the qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
253
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 529 publications
(256 citation statements)
references
References 12 publications
1
253
0
2
Order By: Relevance
“…Hybridization of ANN with other methods will produce very good forecasts [19][20][21]. In [20] an hybrid approach based on ANN and fuzzy logic technique is applied for wind power forecasts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridization of ANN with other methods will produce very good forecasts [19][20][21]. In [20] an hybrid approach based on ANN and fuzzy logic technique is applied for wind power forecasts.…”
Section: Introductionmentioning
confidence: 99%
“…In [20] an hybrid approach based on ANN and fuzzy logic technique is applied for wind power forecasts. In [21], an enhanced hybrid forecasting method that combines the persistence method, the back propagation neural network, and the radial basis function (RBF) neural network, was applied for short-term wind power prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Sideratos et al [61] and Fan et al [59] reported the importance of dividing the dataset into several subsets and fitting a model to each subset.…”
Section: Short-term Wind Power Forecasting Using Nwpmentioning
confidence: 99%
“…In view of this, the electrical power system in China has clearly claimed to bring the active output control of the wind farm into the power network dispatching management [3]. Currently, the electric power system dispatching is mainly based on the short-term wind speed and wind power prediction [4][5][6], which fails to consider the impact of wind turbine (WT) outages on the wind power variation. Meanwhile, there is still a lack of warning information of the WT outages to support the internal coordination control technologies of the wind farm [7,8].…”
Section: Introductionmentioning
confidence: 99%